Effect of graphene addition on the transport critical current density of bulk (Tl0.85Cr0.15) Sr2CaCu2O7-δ superconductor - Kong, Wei; Kong, Ing; Awang Kechik, Mohd Mustafa; Abd Shukor, Roslan (Elsevier, 2018)
In this work, the effect of graphene addition on the transport critical current density of (Tl0.85Cr0.15) Sr2CaCu2O7-δ (Tl-1212) superconductor was investigated. Thallium-based high temperature superconductor (HTS) with nominal starting composition (Tl0.85Cr0.15) Sr2CaCu2O7-δ was prepared using high purity oxide powders via solid state reaction method. 0.001 – 0.005 wt.% of graphene were added into Tl-1212 superconductors. The characteristic of the samples were determined by powder X-ray diffraction method, scanning electron microscopy (SEM), energy dispersive X-Ray analysis (EDX), electrical resistance measurements and transport critical current density measurements. The zero-resistance temperature, Tc-zero was found to decrease from 95 K to 84 K with the increase of graphene. The temperature dependence transport critical current density (Jc) of the pure and graphene added bulk samples were investigated. Jc of the non-added bulk sample was 1320 mA/cm2 at 30 K while the Jc of sample with 0.001 wt.% graphene was 3660 mA/cm2 at 30 K. Results showed that the Jc of the Tl-1212 samples decreased with increasing graphene addition. Graphene acted as impurity which is believed to perform the flux pinning effect to Tl-1212. Thus, the Jc of Tl-1212 superconductors was enhanced. The phase formation and morphology of samples Tl-1212 were also discussed in this paper.